THE INFORMATION MODEL OF POSTGRADUATE STUDENT WITH METHODOLOGICAL COMPETENCE PREPARATION IN THE HIGHER MILITARY EDUCATION SYSTEM - Igor M. Kozubtsov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The author based on an ideal model of graduate reasonably functional meaning methodological competence graduate in higher military education system. Functionality includes all professional activities within the methodological competence. Functionality includes cognitive and activity component. Under the individual properties of graduate and readiness of the organization of professional competency given characteristic. On basis application of the grounded ideal model allowed us to build the ideal model of preparation of postgraduate students with a methodological competence in the system of higher military education. Appropriately to concentrate research on research of choice of technologies of development of methodological competence of postgraduate students in the conditions of an educational-educate process of the system of higher military education.